Peran user education dalam membentuk perilaku siswa pada pencegahan kerusakan koleksi perpustakaan SD IT Salsabila 3 Banguntapan - Ariska Idamayanti (Nur Science Institute, 2026)
This study examines the role of user education in shaping student behavior as users, especially in efforts to prevent damage to library collections. The purpose of this study is to find out how user eduucation is applied in libraries and the extent to which these activities change student behavior in preventing damage to library collections. The method used in this study is a qualitative approach with data collection techniques through in-depth interviews, observation and documentation. This research was conducted for students and librarians at the Darul Ilmi Library of SD IT Salsabila 3 Banguntapan. The results of the study stated that user education has a strategic role in shaping student behavior that is more responsible in maintaining collections and has a high level of awareness. This is shown by the change in student behavior that is more positive after participating in user education activities, although it has not occurred comprehensively to students. The contribution of this research lies in providing an empirical picture of the importance of user education activities as an educational strategy in supporting library management and preventing damage to library collections.